2021
DOI: 10.2991/assehr.k.210227.042
|View full text |Cite
|
Sign up to set email alerts
|

The School Principals’ Role in Education Management at the Regional Level: An Analysis of Educational Policy in the Industrial Revolution 4.0

Abstract: The present study aimed to analyze the education policies in the era of educational reform. This policy is very monumental in the history of education in Indonesia, where enormous authority is given directly to schools. The schools can develop their respective innovations in developing a treatment for students in learning, the authority to determine the learning time, and the autonomy to compile their own learning textbooks according to the agreed curriculum. But the most important thing is to be able to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 12 publications
3
25
0
5
Order By: Relevance
“…This study concluded that learning with MOOCs was adequate for use in physics learning (Busri et al, 2019). The two previous studies were in line with the research results I got, namely, learning with MOOCs received good responses from students (Fathurrochman et al, 2021).…”
Section: Introductionsupporting
confidence: 86%
“…This study concluded that learning with MOOCs was adequate for use in physics learning (Busri et al, 2019). The two previous studies were in line with the research results I got, namely, learning with MOOCs received good responses from students (Fathurrochman et al, 2021).…”
Section: Introductionsupporting
confidence: 86%
“…SMP Negeri 1 Banyuasin III is ready to implement the national exam exemption program by carrying out competency assessments and character surveys. The results of interviews with the school principal, it was found that SMP Negeri 1 Banyuasin III had prepared various tools needed to carry out competency assessments and character surveys [16].…”
Section: Resultsmentioning
confidence: 99%
“…The learning style used is the key to developing learning performance. It needs to be realized how people absorb and dig up information and can make learning and communicating easier in their style (Fathurrochman, et. al., 2021).…”
Section: Learning Stylementioning
confidence: 99%